The association of parasitic infections in pregnancy and maternal and fetal anemia: a cohort study in coastal Kenya. - Elizabeth M McClure; Steven R Meshnick; Peter Mungai; Indu Malhotra; Christopher L King; Robert L Goldenberg; Michael G Hudgens; Anna Maria Siega-Riz; Arlene E Dent (Public Library of Science (PLoS), 2014)
Background Relative contribution of these infections on anemia in pregnancy is not certain. While measures to protect pregnant women against malaria have been scaling up, interventions against helminthes have received much less attention. In this study, we determine the relative impact of helminthes and malaria on maternal anemia. Methods A prospective observational study was conducted in coastal Kenya among a cohort of pregnant women who were recruited at their first antenatal care (ANC) visit and tested for malaria, hookworm, and other parasitic infections and anemia at enrollment. All women enrolled in the study received presumptive treatment with sulfadoxine-pyrimethamine, iron and multi-vitamins and women diagnosed with helminthic infections were treated with albendazole. Women delivering a live, term birth, were also tested for maternal anemia, fetal anemia and presence of infection at delivery. Principal findings Of the 706 women studied, at the first ANC visit, 27% had moderate/severe anemia and 71% of women were anemic overall. The infections with highest prevalence were hookworm (24%), urogenital schistosomiasis (17%), trichuria (10%), and malaria (9%). In adjusted and unadjusted analyses, moderate/severe anemia at first ANC visit was associated with the higher intensities of hookworm and P. falciparum microscopy-malaria infections. At delivery, 34% of women had moderate/severe anemia and 18% of infants' cord hemoglobin was consistent with fetal anemia. While none of the maternal infections were significantly associated with fetal anemia, moderate/severe maternal anemia was associated with fetal anemia. Conclusions More than one quarter of women receiving standard ANC with IPTp for malaria had moderate/severe anemia in pregnancy and high rates of parasitic infection. Thus, addressing the role of co-infections, such as hookworm, as well as under-nutrition, and their contribution to anemia is needed.